(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2015)
Purpose: Laparoscopy is gaining popularity over laparotomy in various surgical conditions. Now a day, an increasing number of diagnostic and therapeutic surgical procedures are being done laparoscopically. The aim of this study was to assess the safety and feasibility of laparoscopy in children. Materials and Methods: This retrospective study was carried out in the Department of Pediatric Surgery of Dhaka Medical College Hospital over a period of 52 (Fifty two) months from June 2009 to August 2013. A total of 123 patients were operated laparoscopically up to 12 years of age for different surgical conditions. Data was collected from the hospital records and analyzed retrospectively. Results: Out of these 123 laparoscopically performed cases, Appendectomy was performed in 39 cases, closure of internal inguinal ring for Inguinal Hernia was done in 36 patients, 20 patients underwent Cholecystctomy, 16 patients had laparoscopic procedures for impalpable Undescended Testis (UDT), 5 patients were operated for Adnexal Mass of which one case was converted into open procedure due to technical difficulties and 1 for Pancreatic Pseudo cyst. Diagnostic Laparoscopy was performed for 2 patients with Biliary Atresia and 4 patients for Ambiguous Genitalia. Median age of the patients was 6.08 years (ranging from 2 months to 12 years of age). The length of post operative hospital stay was 2-3 days. All the laparoscopic procedures for Inguinal Hernia and impalpable UDT were performed as day care surgery. Operative and post operative complications were minimal. Other advantages of the laparoscopic procedures were smaller incisions, incidental diagnosis of other associated pathology, lesser post operative pain, earlier oral feeding, quicker mobilization and a better cosmetic result. Conclusion: With the recent development of laparoscopic surgical techniques and equipments, laparoscopic surgical procedures are becoming popular day by day and can be performed safely for both diagnostic and therapeutic purposes in pediatric surgical patients. J. Paediatr. Surg. Bangladesh 4(1): 11-18, 2013 (January)